A Novel Frameshift Mutation in Abnormal Spindle-Like Microcephaly (ASPM) Gene in an Iranian Patient with Primary Microcephaly: A Case Report - Afsaneh BAZGIR; Mehdi AGHA GHOLIZADEH; Faezeh SARVAR; Zahra PAKZAD (Tehran University of Medical Sciences, 2019)
Autosomal recessive primary microcephaly (MCPH) is a rare genetic disorder, leading to the defect of neurogenic brain development. Individuals with MCPH reveal reduced head circumference and intellectual disability. Several MCPH loci have been identified from several populations. Genetic heterogeneity of this disorder represents molecular testing challenge. An 8 yr old female, born from consanguineous parents, was attended to Fardis Central Lab, Alborz, Iran. Based on the reduced circumference and intellectual disability, MCPH was diagnosed. Whole exome sequencing of the patient identified a novel homozygous frameshift mutation (c.2738dupT, p.Cys914fs) in exon 9 Abnormal Spindle-like Microcephaly )ASPM( gene. By Sanger sequencing, segregation analysis showed that both parents were heterozygous carriers for this variant. The novel frameshift mutation likely truncates the protein, resulting in loss of normal function ASPM in homozygous mutation carriers. The study might add a new pathogenic variant in mutations of the ASPM gene as a causative variant in patients with MCPH and might be helpful in genetic counseling of consanguineous families.